BIMBOFICATION TO EMPOWER: REPRESENTATION OF HYPERFEMININITY ON TIKTOK - Melanie Rosaria; Andika Wijaya (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2022)
Among the diversity of trends and subcultures on TikTok, bimbofication has become a notable phenomenon with its representation of hyperfemininity to dismantle misogyny and patriarchal standards in society. The movement acknowledges and challenges the stigma towards bimbos who are often portrayed as hyperfeminine women, while inviting the audience to engage in traits and attitudes that are associated with the stereotypes. The purpose of the movement is to empower and liberate women from the fear of misogyny. However, due to the layers and complexity in the discussion, bimbofication may provoke mixed interpretations and invite various responses. The complexity of bimbofication can be found in videos posted by Chrissy Chlapecka, a self-proclaimed bimbo figure on TikTok. This paper contributes to gender studies as it explores hyperfemininity representation in relation to the notion of women’s empowerment. Moreover, it also intersects with cultural studies as it examines a social phenomenon on social media, specifically TikTok movement, and how it challenges society's standards. By following Sandelowski purposive sampling method (1995) and Murnen and Byrne’s hyperfemininity scale (1991), it is found that regardless of the ambiguities and varying interpretations, bimbofication has provided a space for women to freely express and explore their unique version of femininity.AbstrakDi antara keragaman tren dan subkultur di TikTok, bimbofication telah menjadi fenomena penting karena representasi hiperfeminitasnya yang membongkar misogini dan standar patriarkis dalam masyarakat. Gerakan ini mengakui dan menantang stigma terhadap bimbo yang sering digambarkan sebagai wanita hiperfeminin sambil mengajak penonton untuk melibatkan diri mereka dengan sifat dan sikap yang terkait dengan stereotip tersebut. Tujuan dari gerakan ini adalah pemberdayaan dan pembebasan perempuan dari ketakutan akan misogini. Namun, karena lapisan-lapisan dan kompleksitas dalam diskusi ini, bimbofication dapat memicu interpretasi yang beragam dan mengundang berbagai macam tanggapan. Kompleksitas bimbofication dapat ditemukan dalam video yang diunggah oleh Chrissy Chlapecka, sosok yang memproklamirkan dirinya sebagai bimbo di TikTok. Artikel ini berkontribusi pada studi gender dengan mengeksplorasi representasi hiperfeminitas dalam kaitannya dengan gagasan pemberdayaan perempuan. Selain itu, penelitian ini juga bersinggungan dengan kajian budaya karena meneliti fenomena sosial di media sosial, khususnya gerakan TikTok, dan bagaimana gerakan ini menantang standar masyarakat. Dengan mengikuti metode purposive sampling dari Sandelowski (1995) dan menggunakan skala hiperfeminitas Murnen dan Byrne (1991), artikel ini menemukan bahwa, terlepas dari ambiguitas dan interpretasi yang berbeda-beda, bimbofication telah memberikan ruang bagi perempuan untuk berekspresi secara bebas dan mengeksplorasi feminitas mereka yang unik.